Implementasi Sistem Informasi Notulen Rapat Dan Penugasan Pegawai Pada Dinas Pangan, Tanaman Pangan Dan Hortikultura - Muhammad, Muhammad; Oktarina, Dwi; Sukrianto, Darmanta; Purjumatin, Purjumatin (Computer Science and Information Technology, 2023)
The minutes of the meeting are recordings made as a conclusion of the discussions that take place in the meeting process, while the appointment of officials is the assignment of duties to officials in accordance with their respective fields. The current recordings of the minutes of the meeting are still done manually; the minutes are recorded closely at the meeting and are stored in the archive of the notes until they are stacked and vulnerable to damage. The current staff assignment is still done manually by the chief of the service, who makes the staff appointment letter, then prints the staff assignments and gives them to the staff through the staff and general officers department, so it will take quite a long time. The methods used in the minutes of the meeting and the appointment of staff are prototype methods where data collection techniques are used, including interviews and observations, whereas the design methods in this design are described as using case diagrams, activity diagrams, sequence diagrams, and class diagrams. The objective of the research is to transform the manual system into a web-based system that can be accessed online as well as to provide ease in managing the minutes of meetings and staff appointments at the Food Plant and Horticulture Service.